A preliminary analysis of the performance of a targeted HIV electronic medical records alert system: A single hospital experience. Issue 1 (January 2021) - Naito, Toshio; Endo, Kanako; Fukushima, Shinichi; Suzuki, Mai; Fukui, Yukiko; Saita, Mizue; Yokokawa, Hirohide
Abstract: Early treatment of HIV relies on a timely detection of the infection, but many people living with HIV/AIDS are unaware of their infection. In the current study, we applied an electronic medical records (EMR)-based alert system flagging high-risk patients previously diagnosed with infections of syphilis, hepatitis A virus, hepatitis B virus, and/or hepatitis C virus, and those aged 20–50 years with a prior diagnosis of shingles. During the study period (April to October 2019), a total of 47 individuals among 22, 264 patients visiting our department were identified as having high-risk of carrying HIV, and 14 of these individuals underwent HIV testing. Two males aged below 65 years with a previous diagnosis of syphilis were subsequently tested positive for HIV. This preliminary analysis of the EMR alert system facilitated the identification of high-risk people possibly carrying HIV, but the test rate remains to be improved.